How do teachers interpret and transform entrepreneurship education?. Issue 4 (4th July 2019) - Fejes, Andreas; Nylund, Mattias; Wallin, Jessica
ABSTRACT: During the last decade, entrepreneurship education has become a central curricular topic in many locations in the world. In Sweden, entrepreneurship education was implemented in the curriculum for the first time in 2011, as something that should be included in all upper secondary school programmes. In this article, we focus on one of these programmes, the handicraft programme, investigating how entrepreneurship education is formulated in the latest curriculum and how teachers understand and transform such content in their teaching. Drawing on Bernstein's concepts of classification and framing, we illustrate how entrepreneurship education in the Swedish curriculum has a 'dual definition', representing very different framing and classification, but still clearly belongs in a 'market relevance' discourse. This is expressed through the way in which the concept is transformed by teachers in their teaching. We also find that entrepreneurship education has low legitimacy among teachers, particularly when it is classified weakly. The weak framing and classification, taken together with the low legitimacy among teachers, are likely to lead to very different transformations of entrepreneurship education in different educational contexts. In the long run, this could have a negative effect on the equivalence of teaching at upper secondary school.